2017
DOI: 10.1016/j.ygyno.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of miliary versus non-miliary sub-staging in advanced ovarian cancer

Abstract: Objective The presence of miliary disease during initial ovarian cancer debulking may reflect a distinct mode of peritoneal spread independent from size-based tumor staging and may explain variation in response to treatment and survival outcomes. To infer the prevalence, presentation and clinical implications of miliary disease we reviewed existing surgical records. Methods Reports were available for 1008 primary debulking surgeries for ovarian, primary peritoneal or fallopian tube cancer between 2001 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
4
15
0
1
Order By: Relevance
“…We reasoned that patients with upper abdominal and miliary disease have similar surgical outcomes and molecular profiles: both are more likely to be MES, and both more often have incomplete resections compared to lower abdominal and pelvic disease. Previous studies have reported on the prognostic significance of miliary disease [20]. However, we observed similar OS between patients with upper abdominal and miliary disease.…”
Section: Discussionsupporting
confidence: 76%
“…We reasoned that patients with upper abdominal and miliary disease have similar surgical outcomes and molecular profiles: both are more likely to be MES, and both more often have incomplete resections compared to lower abdominal and pelvic disease. Previous studies have reported on the prognostic significance of miliary disease [20]. However, we observed similar OS between patients with upper abdominal and miliary disease.…”
Section: Discussionsupporting
confidence: 76%
“…This spread behavior was linked to the putative origin of the cancer, fallopian tube secretory epithelial cells (FTE) or ovarian surface epithelial (OSE) cells [12,13,14]. Patients with miliary spread type and patients with tumors of putative tubal origin have an unfavorable survival outcome [6,8,12,15,16] and would urgently require new targeted therapies. It was also shown that patients with non-miliary tumor spread present with an increased adaptive immune reaction (e.g., CD8 + immune cell tumor infiltration) and immune-checkpoint expression (e.g., PD-L1 on tumor cells) [7], therefore might render good candidates for an additional immune therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, multivariate analysis showed histological subtypes (HR-1.862) and histopathological grade (HR-1.145) were independent prognostic factor for DFS but statistically not significant (p-value< .396 & .785 respectively). 4,11,15 In this study, reported that univariate analysis, histopathological types(HR-1.28095% CI) and grade (HR-1.653 95% CI) was independent significant for recurrence and grade was statistically significant (p<.040). This study showed that mucinous (43.8%) and clear cell(50.0%) subtypes had more recurrence when compared with serous (41.9%) histology.…”
Section: Discussionmentioning
confidence: 69%